2021
DOI: 10.1002/adfm.202100163
|View full text |Cite
|
Sign up to set email alerts
|

Bipyridine Modified Conjugated Carbon Aerogels as a Platform for the Electrocatalysis of Oxygen Reduction Reaction

Abstract: Aerogels offer a great platform for heterogeneous electrocatalysis owing to their high surface area and porosity. Atomically dispersed transition metal ions can be imbedded in these platforms at ultra‐high site density to make them catalytically active for various reactions. Herein, the synthesis of a new class of conjugated microporous organic aerogels that are used as covalent 3D frameworks for the electrocatalysis of oxygen reduction reaction (ORR) is reported. Modified aerogels functionalized with bipyridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…51,52 The absorption peaks of the pyridine ring's C−H out-of-plane bending vibration and in-plane deformation vibration were detected at 790, 828, and 1012 cm −1 in pyridine-N x C. The skeletal vibration of the pyridine ring was ascribed to the characteristic peaks at 1460 and 1585 cm −1 . 53 The characteristic peak at 1030 cm −1 in ben-C was attributed to the in-plane bending vibration of aromatic C−H. Typical peaks of the skeletal vibration of the benzene ring were also found at around 1400−1600 cm −1 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…51,52 The absorption peaks of the pyridine ring's C−H out-of-plane bending vibration and in-plane deformation vibration were detected at 790, 828, and 1012 cm −1 in pyridine-N x C. The skeletal vibration of the pyridine ring was ascribed to the characteristic peaks at 1460 and 1585 cm −1 . 53 The characteristic peak at 1030 cm −1 in ben-C was attributed to the in-plane bending vibration of aromatic C−H. Typical peaks of the skeletal vibration of the benzene ring were also found at around 1400−1600 cm −1 .…”
Section: Resultsmentioning
confidence: 95%
“…The peak at 1497 cm –1 corresponded to the CC stretching vibration in the benzene ring, and the peak at 1597 cm –1 was attributed to the in-plane bending vibration of N–H. The band at about 3379 cm –1 was formed by the nitrogen protonation-induced N–H tensile vibration. , The absorption peaks of the pyridine ring’s C–H out-of-plane bending vibration and in-plane deformation vibration were detected at 790, 828, and 1012 cm –1 in pyridine -N x C. The skeletal vibration of the pyridine ring was ascribed to the characteristic peaks at 1460 and 1585 cm –1 . The characteristic peak at 1030 cm –1 in ben -C was attributed to the in-plane bending vibration of aromatic C–H.…”
Section: Resultsmentioning
confidence: 97%
“…Since the HER kinetics with these catalysts is at least a couple of orders of magnitude lower than that of PGMs, several approaches have been proposed to compensate for that. One promising approach is increasing the catalytic site density, by designing and synthesizing three-dimensional frameworks such as metal organic frameworks (MOFs) and covalent organic frameworks (COFs). , …”
Section: Recent Developments Of Pgm-free Catalysts For Hermentioning
confidence: 99%
“…The same trend could be expanded to a Co porphyrin-ethylene COF, which also shows 90% selectivity toward H 2 O formation and better activity compared to the pure carbon-supported Co porphyrin without direct covalent bonds between the macrocyclic units . The uncovered relations between the charge transfer almost certainly extend far beyond the porphyrins and include polycorroles, Co bipyridine-based aerogels, and other polymerized complexes. We must note that it was Collman et al who first demonstrated the governing role of interfacial electron flux in ORR selectivity catalyzed by model Fe porphyrin catalysts. , However, the latter studies were performed on simpler systems where the purely heterogeneous intermolecular charge migration is either nonexistent or mediated by a homogeneous charge carrier . Finally, the maximum selectivity to the 4e – pathway we were able to achieve is 47%, which most likely stems from our reliance on alkaline electrolytes to prevent premature deactivation of the catalysts. , …”
Section: Resultsmentioning
confidence: 82%